NILAI ESTETIKA TARI DAMPENG PADA MASYARAKAT MUARA PEA DESA BUKIT HARAPAN KABUPATEN ACEH SINGKIL - Linda Novali Sihotang (Gesture: Jurnal Seni Tari, 2016)
Dampeng dance is a dance that tumbuhdanberkembang in Aceh Singkil. Dampengcustomary sudahpadatahun inimerupakantarian 1986. The purpose of this study isto discuss the dampeng dance from the perspective of aesthetic value.The theory used in this research is the aesthetic theory of Dhrasono whichcontains about: motion, fashion poetry and music. This theory is a reference tostrip existing problems in Dampeng dance.When the study to discuss Dampeng dance performed during the three months,from mid-December 2015 to February 2016. The research in the village of BukitHarapan. Subdistrict Gunung Meriah. The population is two persons namelyspeakers and artists, who know about the culture Singkil. Samples are numberedtwo people are a resource and artists in the district of Aceh Singkil.Teknik datacollection include observation, interviews, literature study and documentation.Dampeng aesthetics of the dance are the motions of martial that have governancerules, the satisfaction score and the value of togetherness for the people of AcehSingkil. Having yangtinggi excellent value for people who feel that the danceSingkil Dampeng is partly art and cultural preservation is still there and is stillknown to the public sampek Aceh Singkil. Dance dampeng also has aesthetic infashion is clothing with the colors of firm and soft, the color of clothing also hascharacter. It's all evidence of their love of their culture. Of these colors Singkilcommunity admire and maintain Dampeng dance clothing for use by generationsto always be worn when dancing.